Preliminary Clinical Study of a Polyherbal Formulation (Wh1) in the Treatment of Vaginitis - Bapat, Vishnu; Alfred, Leena; Rani R.H, Shobha; T. Ksheerasagar, Pushpa.; Hegde, Geetha; K. Lund, Soumya. (Indian Journal of Pharmacy Practice)
Vaginitis is a very common disease affecting millions of women each year with multifactorial etiology. If left untreated it can lead to various complications. Current medical therapy may temporarily reduce infection but tend to disrupt the normal vaginal flora. Hence, herbal therapy is gaining popularity in women on account of its reduced side effects and restoration of the normal vaginal flora. With this in view, a preliminary clinical study was conducted using a polyherbal formulation (WH I), containing herbs with antifungal, antibacterial, antiseptic and astringent properties. In this prospective clinical study, 36 patients presented with the symptoms of vaginitis of varying etiology were treated successfully with the polyherbal formulation (WH I) and was found to be safe and effective (83%). The results of this study were found to be significant, thus this study will be extended on a large patient population in future
Keywords: Vaginitis; Polyherbal preparation (WH 1); Clinical Study; Female; bacterial vaginosis